Evaluasi Usability Aplikasi Mamikos Menggunakan Metode Use Questionnaire dan Think Aloud Usability Testing - Gusti, I Gusti Gek Sintya Putri; I Made Dwi Budiana Penindra; I Wayan Bandem Adnyana (JURNAL RISET DAN APLIKASI TEKNIK INDUSTRI, 2025)
The use of mobile-based applications has become an integral part of everyday life. One very popular application in this category is Mamikos, which makes it easy to search for boarding houses online with various inspiring and user-friendly features. Even though Mamikos is well known by many groups, there are still several problems faced by users when using this application. Some users reported difficulty in navigation, inaccurate search information, and inadequate application response speed. This research aims to spread the usefulness of the Mamikos application using the Objective Evaluation method, USE Questionnaire, and Think Aloud Usability Testing. The USE Questionnaire method is used to collect quantitative data regarding usability, ease of use, ease of learning, and user satisfaction. Meanwhile, the Think Aloud Usability Testing method is used to gain qualitative insights from users as they use the application. The research results show that the Mamikos application has a good level of usability with an average score of 76% for completing tasks. The usability evaluation that has been tested shows that the Mamikos application has a feasibility score of 59% in the Usability aspect, 70% in the Ease of Use aspect, 55% in the Ease of Learning aspect, and 72% in the Satisfaction aspect. However, some navigation problems and inaccurate information retrieval were still encountered. Based on these findings, recommendations for improvements are provided to improve the user experience.